Anatomy & physiology - Seeley, Rod R. (McGraw-Hill, 2006)
"Anatomy and Physiology, Seventh Edition" was designed to help students develop a solid, basic understanding of anatomy and physiology without an encyclopedic presentation of detail. Great care has been taken to select important concepts and to carefully describe the anatomy of cells, organs, and organ systems. The basic recipe that has been followed for seven editions of this text is to combine clear and accurate descriptions of anatomy with precise explanations of how structures function, and examples of how they work together to maintain life. To emphasize the concepts of anatomy and physiology, the authors provide explanations of how the systems respond to aging, changes in physical activity, and disease, with a special focus on homeostasis and the regulatory mechanisms that maintain it. Timely and interesting examples demonstrate the application of knowledge in a clinical context.